2021
DOI: 10.1002/advs.202100968
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Quick Setting Nonswelling Hydrogels via Brush Polymers

Abstract: Brush polymers have emerged as components of novel materials that show huge potential in multiple disciplines and applications, including self‐assembling photonic crystals, drug delivery vectors, biomimetic lubricants, and ultrasoft elastomers. However, an understanding of how this unique topology can affect the properties of highly solvated materials like hydrogels remain under investigated. Here, it is investigated how the high functionality and large overall size of brush polymers enhances the gelation kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
(48 reference statements)
2
15
0
Order By: Relevance
“…Transmission electron microscopy (TEM) shows that pacMEL Clv exhibits a globular structure with a dry-state diameter of 23 ± 3 nm, which is in line with dynamic light scattering (DLS) analysis (a D h of 34.1 ± 0.4 nm, Figure C,D). The observed globular morphology of pacMEL is the result of the collapse of the hydrophobic polynorbornene backbone in aqueous solution, which has been reported in other studies and simulations. , Considering the number of the side chains (DP n ∼ 30) in our design, the polymer used in pacMEL has entered the bottlebrush regime and should offer stronger steric inhibition of external macromolecules than the slightly branched star polymers. , Y PEG-MEL exhibits an expected smaller cumulant D h of 21.0 ± 0.5 nm. ζ-potential measurements indicate that PEGylation reduces the overall positive charge of MEL, especially by the bottlebrush PEG; both the pacMELs exhibit a near-neutral ζ-potential (0.3 mV) compared with natural MEL (∼8 mV, Figure E).…”
Section: Results and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) shows that pacMEL Clv exhibits a globular structure with a dry-state diameter of 23 ± 3 nm, which is in line with dynamic light scattering (DLS) analysis (a D h of 34.1 ± 0.4 nm, Figure C,D). The observed globular morphology of pacMEL is the result of the collapse of the hydrophobic polynorbornene backbone in aqueous solution, which has been reported in other studies and simulations. , Considering the number of the side chains (DP n ∼ 30) in our design, the polymer used in pacMEL has entered the bottlebrush regime and should offer stronger steric inhibition of external macromolecules than the slightly branched star polymers. , Y PEG-MEL exhibits an expected smaller cumulant D h of 21.0 ± 0.5 nm. ζ-potential measurements indicate that PEGylation reduces the overall positive charge of MEL, especially by the bottlebrush PEG; both the pacMELs exhibit a near-neutral ζ-potential (0.3 mV) compared with natural MEL (∼8 mV, Figure E).…”
Section: Results and Discussionsupporting
confidence: 75%
“…The observed globular morphology of pacMEL is the result of the collapse of the hydrophobic polynorbornene backbone in aqueous solution, which has been reported in other studies and simulations. 32,33 Considering the number of the side chains (DP n ∼ 30) in our design, the polymer used in pacMEL has entered the bottlebrush regime and should offer stronger steric inhibition of external macromolecules than the slightly branched star polymers. 21,34 Y PEG-MEL exhibits an expected smaller cumulant D h of 21.0 ± 0.5 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In other words, the degree of valency or f for each brush polymer can be specified as a function of the brush polymer synthesis, thereby providing a good model to study the influence of f on the hydrogel behavior. A preliminary study has now demonstrated that cross-linking the arms of water-soluble brush polymers can indeed induce interesting properties in the resulting gels. , For example, these hydrogels exhibited rapid gelation (100-fold increase in gelation rate compared with 4-arm star polymers of an identical arm length) and nearly entirely nonswelling behavior at body temperature (∼37 °C). Because these properties make brush polymer gels potentially beneficial in different biomedical applications, it is important to further investigate the relationship between the brush polymer design and the properties of resulting hydrogels to understand how the brush topology affects the gel behavior in a more systematic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Such features of BB polymers have stimulated researchers to develop various functional materials, including ultrasoft elastomers 2,3 exhibiting mechanochromism 4 or reprocessability, 5 nanoporous materials, 6 polymer ink with tunable structural color, 7 and quick-setting hydrogels. 8 In particular, elastomers and gels formed by cross-linking of BB polymers have been studied extensively because the unique chain architecture directly influences mechanical properties. The seminal work by Vatankhah-Varnosfaderani 3 showed that the use of BB polymers as components of network polymers enabled soft and strain-stiffening mechanical responses similar to biological tissues, which were inaccessible for conventional gels and elastomers.…”
Section: Introductionmentioning
confidence: 99%